2007
DOI: 10.1016/j.bbrc.2006.11.070
|View full text |Cite
|
Sign up to set email alerts
|

Collagen expression in fibroblasts with a novel LMNA mutation

Abstract: Laminopathies are a group of genetic disorders caused by LMNA mutations; they include muscular dystrophies, lipodystrophies and progeroid syndromes. We identified a novel heterozygous LMNA mutation, L59R, in a patient with the general appearance of mandibuloacral dysplasia and progeroid features. Examination of the nuclei of dermal fibroblasts revealed the irregular morphology characteristic of LMNA mutant cells. The nuclear morphological abnormalities of LMNA mutant lymphoblastoid cell lines were less promine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
0
17
0
4
Order By: Relevance
“…31,32 In addition, human p.L59R LMNA-mutated fibroblasts did not demonstrate the physiologic decrease in collagen production during aging. 33 Therefore, LMNA mutations and/or altered prelamin A maturation could lead to altered extracellular matrix production, which could participate in adipose tissue dystrophy. However, inasmuch as we observed that adipose tissue fibrosis was also present in mtDNA-mutated lipomas and in buffalo humps from patients not treated using protease inhibitors, a role for prelamin A in that setting is not likely.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 In addition, human p.L59R LMNA-mutated fibroblasts did not demonstrate the physiologic decrease in collagen production during aging. 33 Therefore, LMNA mutations and/or altered prelamin A maturation could lead to altered extracellular matrix production, which could participate in adipose tissue dystrophy. However, inasmuch as we observed that adipose tissue fibrosis was also present in mtDNA-mutated lipomas and in buffalo humps from patients not treated using protease inhibitors, a role for prelamin A in that setting is not likely.…”
Section: Discussionmentioning
confidence: 99%
“…Авторы предположили диагноз атипичного син-дрома Вернера, но мутаций в гене RECQL2, ассоци-ированном с этой патологией, не выявили. Позже идентифицировали гетерозиготную миссенс мута-цию в гене LMNA (L59R) и диагностировали ламино-патию как нетипичную форму акромандибулярной дисплазии [12]. McPherson Е, et al в 2009г повторно обследовали пациентку и дополнительно сообщили о наличии эндокринологической патологии, в том числе о преждевременной недостаточности яичников и вторичной аменорее, возникших в возрасте 15 лет.…”
unclassified
“…McPherson Е, et al в 2009г повторно обследовали пациентку и дополнительно сообщили о наличии эндокринологической патологии, в том числе о преждевременной недостаточности яичников и вторичной аменорее, возникших в возрасте 15 лет. Было выявлено неполноценное развитие вторичных половых признаков и повышение в сыворотке крови уровней ФСГ и ЛГ, а при УЗИ органов малого таза были обнаружены репродуктивные аномалии (маточно-яичниковая инфантильность) [12,13].…”
unclassified
See 2 more Smart Citations